1983
DOI: 10.1128/aem.45.1.122-126.1983
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among fecal coliforms, Escherichia coli, and Salmonella spp. in shellfish

Abstract: The relationship of fecal coliforms, Escherichia coli, and Salmonella spp. was examined in freshly harvested and stored shellfish. In 16 of 40 freshly collected oyster samples, fecal coliform levels were above the recommended wholesale level suggested by the National Shellfish Sanitation Program ('230/100 g), and Salmonella spp. were present in three of these samples. Salmonella spp. were not, however, present in any sample containing less than 230 fecal coliforms per 100 g. Analysis of the data suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 17 publications
(12 reference statements)
2
14
0
Order By: Relevance
“…This study has shown E. coli to be an adequate indicator of S. newport in various freshwater sediments and supports many investigations on Salmonella spp. and E. coli survival in water and soil ecosystems (1,2,12,22,32). Although rates vary greatly among soil, water, and sediment media, E. coli has usually been observed to survive as long as or longer than Salmonella spp., thus fulfilling an essential requirement for an indicator of pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown E. coli to be an adequate indicator of S. newport in various freshwater sediments and supports many investigations on Salmonella spp. and E. coli survival in water and soil ecosystems (1,2,12,22,32). Although rates vary greatly among soil, water, and sediment media, E. coli has usually been observed to survive as long as or longer than Salmonella spp., thus fulfilling an essential requirement for an indicator of pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…With increased demands on water resources, problems of contamination of surface water and groundwater by enteric microorganisms have become an increasing concern. Although enumeration of coliforms and fecal coliforms is used to assess the quality of water used for drinking, shellfish harvesting, and recreation, the validity of methods for estimating the presence of human pathogens has been questioned (14,20). Direct detection of waterbome pathogens, rather than indicator organisms, has not been adopted as a standard method in the United States (2) because, in general, enumerative schemes for enteric pathogens involve timeconsuming, expensive methods which often yield equivocal results.…”
mentioning
confidence: 99%
“…Examination of water samples for pathogens are usually carried out because many workers have found positive correlation between high density viable counts, total and fecal coli forms and the presence of pathogens such as Salmonella, E. coli, S. aureus in drinking water (Hood et al, 1983;LeChevallier, 1990;Payment et al, 1993). Moreover, there have been reported cases of food and waterborne disease outbreaks in both children and adults in Southeastern Nigeria (Blum et al, 1987;Ogan, 1988).…”
Section: Introductionmentioning
confidence: 99%